Empowering community connection: building a support network through low-code product development - a social entrepreneurship perspective - Butler, William Alexander (2023)
This field lab in collaboration with SPEAK, a social impact venture, provides a practical approach at Low-Code product development for the inclusion process of newcomers through a mobile application. Using a design thinking approach and drawing on research on social entrepreneurship. The results inform the target user preferences, the complex dimensions of their integration process and are translated into prioritised product features. These are validated with target users and conclude in the creation of a mobile application minimum viable product.